Cover Image, Volume 55, Issue 4. Issue 4 (15th February 2017) - Unknown
Abstract : In honor of Professor Ben Zhong Tang's 60th birthday, this special issue features an array of articles from his good friends, students, and colleagues. The front cover shows Professor Tang hard at work in his office at Hong Kong University of Science and Technology in 2011, delivering a talk on Aggregation‐Induced Emission in 2010, and of course, sharing his passion with his students at South China University of Technology in the summer of 2016. The growth of his students and the success of his collaborators are the source of his happiness, which is evident in his photos.